(untitled) (Al-Qamar, 2018)
Gender is institutionalized by prevalent social values and cultural traditions in a region. The present study intends to analyze various structural factors that might be proven beneficial or disadvantageous for the two genders (male and female). It is a matter of common observation that when one of the genders occupies dominant positions and receives recognition then usually it is at the expense of the other one. The first section highlights social structural factors related with the differential treatment towards gender and recommends so the situation can be made better by formation and implementation of policies and Islamic law in the country. The second half of the paper discusses various Islamic provisions that enlighten about the gender roles and rights. Multiple examples of women participation in various fields have been excerpted from Islamic history for further elaboration. It is concluded that most of our societal behaviour is in contradiction with Islamic teachings and we being Muslims need to revisit our social practices in the light of the religious guidelines.